Activating community-based Indigenous language and culture resources for university teaching : report on the development of a digital shell and pilot delivery - Bow, Cathy; Department of Education and Training (Canberra, ACT : Department of Education and Training, 2017)
The project team had worked successfully with the online delivery of NT East Arnhem land Yolŋu languages for many years, and used seed funding from the OLT/PELTHE to fund the engagement of Bininj (Indigenous) elders in West Arnhem Land for the development, delivery and evaluation of an online course in Bininj Kunwok language, alongside the development of a template for other groups to use to share their own language.
Includes bibliographical references (pages 31-32)
Keywords: Australian languages -- Study and teaching -- Northern Territory; Australian languages -- Northern Territory; Aboriginal Australians -- Languages; Web-based instruction -- Research and development projects -- Northern Territory; Computer-assisted instruction -- Northern Territory; Internet in education -- Australia; Australian